STRATEGI PERLINDUNGAN FLORA DAN FAUNA HUTAN MENGHADAPI ANCAMAN PERUBAHAN IKLIM DAN DEGRADASI LINGKUNGAN - John F. Sahusilawane; Wilma Imlabla (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Climate change demands sustainable adaptive strategies to maintain ecosystem resilience and human well-being. This study employs the Systematic Literature Review (SLR) method combined with bibliometric analysis to examine the development of literature on ecosystem-based adaptation (EbA). Data were obtained from the Scopus database within a specific time range and analyzed using VOSviewer through three stages: co-occurrence analysis to identify main research themes, co-authorship analysis to map collaboration networks among authors and institutions, and co-citation analysis to reveal conceptual linkages across studies. The results show that EbA has become an integrative framework emphasizing ecosystem-based conservation, community engagement, and the utilization of monitoring technologies such as remote sensing, GIS, drones, and artificial intelligence. Patterns of international collaboration highlight the critical role of synergy among government policies, community practices, and academic recommendations in strengthening adaptive strategies. This study concludes that the success of EbA requires a combination of scientific approaches, technological innovation, and active community participation to achieve sustainable adaptation.